A personalized requirement identifying model for design improvement based on user profiling. Issue 1 (27th February 2020) - Li, Jing; Zhang, Xinwei; Wang, Keqin; Zheng, Chen; Tong, Shurong; Eynard, Benoit
Abstract: The personalization of products and services has become an inevitable trend in the manufacturing and service industry, but it is very difficult to identify users' personalized requirements accurately. This paper solves this problem by constructing an identifying model for personalized requirement based on user profiling. Firstly, the framework of the proposed model and the process of identifying the user's personalized requirements with this model are introduced, and then an experimental scheme for obtaining users' profiling data is designed. On this basis, an experiment is performed by investigating users' requirements for the computer to obtain the data, and the data are used for the analysis based on the proposed model. The analysis result shows that the model can reveal the difference among heterogeneous users well, find out the implicit requirements of users, and identify the gap between existing products and users' personalized requirements, which provides support to the subsequent improvement of product design.